2007
DOI: 10.1002/jrs.1683
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic origin and temperature dependence of Raman optical redshift in nanostructures: a broken bond rule

Abstract: Consistent insight is presented into the atomistic origin and temperature (T) dependence of the redshift of Raman optical modes in nanostructures from INTRODUCTIONThe vibration of under-coordinated atoms at a surface and in a nanosolid is of great importance because the behavior of surface phonons influences directly the electrical, optical, and dielectric properties in semiconductor materials and devices, such as electron-phonon coupling, photoabsorption, and photoemission, as well as phonon scattering in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…The other two peaks observed at 276 and 595 cm −1 are the results of the host lattice defects. In addition, at P O = 0 sccm, the peak near 408 cm −1 shifts to 418 cm −1 , and there appears such a weak peak at 380 cm −1 because the optical modes of the Zn-O bonds can be decided by the bond length, bond angle, bond strength, and atomic coordination numbers [29]. There are defects in the films fabricated at P O = 0 sccm so that the bond length, bond angle and bond strength of the Zn-O bonds can be affected.…”
Section: Morphology and Microstructurementioning
confidence: 94%
“…The other two peaks observed at 276 and 595 cm −1 are the results of the host lattice defects. In addition, at P O = 0 sccm, the peak near 408 cm −1 shifts to 418 cm −1 , and there appears such a weak peak at 380 cm −1 because the optical modes of the Zn-O bonds can be decided by the bond length, bond angle, bond strength, and atomic coordination numbers [29]. There are defects in the films fabricated at P O = 0 sccm so that the bond length, bond angle and bond strength of the Zn-O bonds can be affected.…”
Section: Morphology and Microstructurementioning
confidence: 94%
“…The population of non‐equilibrium phonons decays into lower energy phonons as an effect of the anharmonic interaction or is scattered by the thermal phonons into modes with different frequencies. These phonon–phonon interactions are of special interest in nanostructured systems due to the lack of an adequate description in the literature . Previous studies have shown that the Raman properties of materials at high temperature are size dependent .…”
Section: Introductionmentioning
confidence: 99%
“…Any frequency shift or the variation of the half--width Γ with temperature of the Raman modes are the measurements of the anharmonicity of the interactions. The phonon-phonon interactions are of special interest in nanostructured systems if we have in mind that in the literature there is still no adequate theory which describes the anharmonic effects in these systems [5,6].…”
Section: Introductionmentioning
confidence: 99%